Optimal Unit Sizing of Biogas-Fuelled Micro Gas Turbine Cogeneration Systems in a Sewage Treatment Plant - F., Basrawi; Hassan, Ibrahim; Yamada, Takanobu (Elsevier Ltd, 2015)
This paper investigates the optimum size of Micro Gas Turbine Cogeneration Systems (MGT-CGSs) in a sewage treatment plant in relation to its economic performance. A sewage treatment plant in a cold region was adopted as a model, and three units of MGT-CGS with power output capacity of 30, 65 and 200 kW were simulated to utilize biogas produced in-house in the plant. The energy balance of the system was first studied, and economic performance using Net Present Value method was carried out. It was found that a configuration with optimum combination of 3 types of MGTs (MGT-Combined) stated above had the highest power generation efficiency. However, MGT-Combinedneededmore units of MGT resulting in higher capital investment. Although all configurations of MGT-CGSs studied can generate Net Present Value (NPV) in the range of US$2,640,000-3,100,00, MGT-200had the highest NPV. MGT-200 had15% higher NPV compared to the lowest one,MGT-30. MGT-200 can generate the highest NPV because it had thelowest capital investment cost, while having high power cost savings.